Minimally invasive surgery for hallux valgus treatment: Temporal analysis of scientific literature - Rocha, John Victor; fonseca, elizabeth; Molina, Wellington Farias; Martins , Guilherme Bottino; Heitzmann, Lourenço Galizia (Journal of the Foot & Ankle, 2024)
Objectives: Investigate the growth of scientific publications on minimally invasive surgery techniques for hallux valgus treatment, perform a comparative analysis of the adoption of these methodologies by orthopedic surgeons, and provide a statistical prediction of future publications. Methods: A time series of scientific publications was used between 2000 and 2023, with data collected on the PubMed platform. Least squares determined the linear trend by analyzing the publications that mention minimally invasive and open surgical techniques. Articles in Portuguese and English addressing surgical techniques for hallux valgus treatment were considered. Results: The analysis included 997 articles, showing a substantial increase in publications on minimally invasive techniques over the past five years. The Chevron technique is the most cited among open surgeries (178 references). Articles addressing minimally invasive techniques went from 1 in 2000 to 54 in 2023. Predictions indicate continued growth in publications on minimally invasive surgery through 2030. Conclusion: There is a growing trend in the scientific literature supporting minimally invasive techniques for hallux valgus correction. The comparison between minimally invasive and open techniques has intensified and highlights the need to evaluate their applications to provide the best clinical outcomes. This study contributes to a better understanding of the evolution and adoption of these techniques in orthopedic surgical practice. Level of Evidence IV.